2004
DOI: 10.1128/aac.48.6.1941-1947.2004
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the In Vivo Pharmacodynamic Profile of Cefepime against Extended-Spectrum-Beta-Lactamase-Producing Escherichia coli at Various Inocula

Abstract: Cefepime was evaluated in vivo against two inoculum sizes of four strains of Escherichia coli that produced extended-spectrum beta-lactamases (ESBLs) in a murine neutropenic thigh infection model to characterize the pharmacodynamic activity of cefepime in the presence of ESBL-producing bacteria and to evaluate if differences in lengths of cefepime exposure are required with various inocula. Three strains possessed a single enzyme each: TEM-10, TEM-12, and TEM-26. The fourth strain possessed two TEM-derived ESB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 13 publications
4
40
0
Order By: Relevance
“…Interestingly, in the previous study, regrowth was observed of an isolate with a MIC of 8 mg l 21 even when the %f TwMIC remained above 40 % (50-69 %), leading to the conclusion that specific or co-existent resistance mechanisms may alter the pharmacodynamics of meropenem. However, in vivo studies demonstrated that, regardless of the production of b-lactamases and other meropenem resistance mechanisms, the desired bactericidal effect can still be achieved as long as the drug exposure is 40 % f TwMIC, as also found with the VIM-1-producing isolates used in the present study (Maglio et al, 2004). Our in vivo data are in line with previous data in a neutropenic animal model of thigh infection by extended-spectrum b-lactamase-producing K. pneumoniae isolates treated with meropenem, where c.f.u.…”
supporting
confidence: 63%
“…Interestingly, in the previous study, regrowth was observed of an isolate with a MIC of 8 mg l 21 even when the %f TwMIC remained above 40 % (50-69 %), leading to the conclusion that specific or co-existent resistance mechanisms may alter the pharmacodynamics of meropenem. However, in vivo studies demonstrated that, regardless of the production of b-lactamases and other meropenem resistance mechanisms, the desired bactericidal effect can still be achieved as long as the drug exposure is 40 % f TwMIC, as also found with the VIM-1-producing isolates used in the present study (Maglio et al, 2004). Our in vivo data are in line with previous data in a neutropenic animal model of thigh infection by extended-spectrum b-lactamase-producing K. pneumoniae isolates treated with meropenem, where c.f.u.…”
supporting
confidence: 63%
“…More specifically, the in vivo murine model and pharmacodynamic analyses of results were used to discern the impacts of echinocandin dose, MIC, and fks-1 or fks-2 mutation on treatment effect. These approaches have recently demonstrated utility in defining the clinical relevance of bacterial resistance mutations, design of susceptibility breakpoints, and optimal treatment strategies (4,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Those in favor of changing cephalosporin breakpoints dispute that the inoculum effect is important (231). A final argument in favor of ongoing efforts aimed at ESBL detection is the infection control significance of detecting plasmid-mediated multidrug resistance.…”
Section: Need For Clinical Microbiology Laboratories To Detect Esbl Pmentioning
confidence: 99%